2016
DOI: 10.1590/s1980-6574201600030011
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive effects of resistance exercise with continuous and intermittent blood flow restriction

Abstract: Abstract--The aim of this study was to compare the acute effects of low-intensity (LI) resistance exercise (RE) with continuous blood flow restriction (CBFR) and intermittent blood flow restriction (IBFR) on systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP). After a one-repetition maximum test, 10 normotensive recreationally trained men performed three experimental protocols. In the three RE protocols, increases in SBP, DBP, and MAP were observed immediately after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Only one study 19 included in our systematic review utilized an intermittent application approach, whereas all other studies had the BFR application on continuously 20‐23 . Intermittent application involves deflation of the cuffs during the intra‐exercise rest period when multiple sets of exercise are performed and may be an alternative approach for individuals with medical risk factors to obtain the benefits of LIRE‐BFR exercise without the heightened cardiovascular and hemodynamic responses 48 . A single study showed that maintaining cuff pressure during the rest periods significantly increased post‐exercise release of noradrenaline as well as brachial measures of blood pressure using a failure‐type leg extension LIRE‐BFR protocol, although the loads (20% 1RM vs. 40% 1RM) and cuff type (Hokanson vs. KAATSU) were different 49 from those of Figueroa et al 19 As intra‐exercise brachial systolic and diastolic blood pressures are heightened in a continuous application mode compared with the same exercise performed without blood flow restriction, 15 intermittent application may be a suitable strategy to reduce cardiovascular and hemodynamic stress 48 …”
Section: Discussionmentioning
confidence: 99%
“…Only one study 19 included in our systematic review utilized an intermittent application approach, whereas all other studies had the BFR application on continuously 20‐23 . Intermittent application involves deflation of the cuffs during the intra‐exercise rest period when multiple sets of exercise are performed and may be an alternative approach for individuals with medical risk factors to obtain the benefits of LIRE‐BFR exercise without the heightened cardiovascular and hemodynamic responses 48 . A single study showed that maintaining cuff pressure during the rest periods significantly increased post‐exercise release of noradrenaline as well as brachial measures of blood pressure using a failure‐type leg extension LIRE‐BFR protocol, although the loads (20% 1RM vs. 40% 1RM) and cuff type (Hokanson vs. KAATSU) were different 49 from those of Figueroa et al 19 As intra‐exercise brachial systolic and diastolic blood pressures are heightened in a continuous application mode compared with the same exercise performed without blood flow restriction, 15 intermittent application may be a suitable strategy to reduce cardiovascular and hemodynamic stress 48 …”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that evaluated the application of BFR, only one study analyzed muscle strength and hypertrophy (Fitschen et al, 2014); however, this study used only one exercise with unilateral and single-joint execution. Although some studies have shown no significant differences between continuous and intermittent BFR in the muscle strength and hypertrophy of lower limbs (Fitschen et al, 2014), the muscle activation of the upper limbs (Yasuda et al, 2013) and the hemodynamics of the upper limbs (Neto et al, 2016a;2017b), the best strategy for ST sessions combined with BFR (continuous or intermittent) with the aim of increasing muscle hypertrophy (MH), dynamic muscular strength (DMS), isometric muscle strength (IMS) and localized muscle endurance (LME) of the upper limbs has still not been defined.…”
Section: Introductionmentioning
confidence: 94%
“…This method has been used to increase muscle hypertrophy (Laurentino et al, 2012;Vechin et al, 2015), muscle strength (Laurentino et al, 2012;Silva et al, 2015;Vechin et al, 2015;Sousa et al, 2017) and localized muscle endurance (LME) (Kacin & Strazar, 2011;Gil et al, 2017;Sousa et al, 2017). In addition, it has been used to increase functional capacity (Araujo et al, 2015) and isometric force (Chaves et al, 2016) and has been shown to be safe in relation to hemodynamics (Araújo et al, 2014;Neto et al, 2015;2016a;2016b;Vilaça-Alves et al, 2016;Neto et al, 2017a;2017b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations